Determinants of in-stent restenosis in coronary artery disease patients after percutaneous coronary intervention in Dr Saiful Anwar General Hospital, Malang - Pramudya, Astrid; Rohman, Mohammad Saifur; Novi, Kurnianingsih; Djanggan, Sargowo; Setyasih, Anjarwani (Heart Science Journal, 2026)
Background: In-stent restenosis (ISR) is common complication found following percutaneous coronary intervention. It can be caused by multifactorial such as patient related, lesion related and procedure related. Methods: A retrospective cohort study in Saiful Anwar general Hospital to know what are the characteristic of patient with ISR stated from clinical, lesion and procedural related. Result: From 3335 patients underwent PCI in our hospital, the incidence of ISR after PCI was 9.3%. Stent overlapped as one of the significant predictors of ISR (p=0.024). Multivariate analyses found significant correlation between Multivessel disease (OR = 1.76, 95%; [CI] [1.61 – 1.91], P 0.003), LAD lesion (OR=3.46, 95% CI [2.22 – 5.38], P<0.001), osteal lesion (OR=3.97, 95% CI [2.42-6.52], P<0.001], bifurcation lesion (OR=5.14, 95% CI [2.52-10.49], P<0.001), Calcified lesion (OR=1.86, 95% CI [1.62-2.15], P<0,001), LM disease (OR=2.16, 95% CI [1.36-3.41], P 0.001), Stent overlapped (OR 1.96, 95% CI [1.27-3.02], P 0.03), Stent length (OR=2.08, 95% CI [2.02-3.19] P 0.001). The multi-factor logistic regression analysis suggested that LAD lesion (p<0.001), stent overlapped (p 0.024) and calcified lesion (p<0.001) were independent risk factors for ISR. We evaluate subclinical analysis for stent length cut off >33.5 mm increased the risk of ISR with fair sensitivity but less specificity. Patient with DM type II had 3.013 times folded to become ISR rather than non DM group (1.995 – 4.552, 95% CI). By using ROC Curve, we evaluate subclinical analysis for HbA1C cut off <7.45 % with high sensitivity (81.2 %) and specificity (85.5 %). Conclusion: DM type 2, LAD lesion, stent overlapped and calcified lesion were the determinant of ISR.